Relative wage positions and quit behavior: New evidence from linked employer-employee data - Christian Pfeifer; Stefan Schneck (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
We use a large linked employer-employee data set to analyze the importance of relative wage positions in the context of individual quit decisions as an inverse measure of job satisfaction. Our main findings are: (1) Workers with higher relative wage positions within their firms are on average more likely to quit their jobs than workers with lower relative wage positions; and (2) workers, who experience a loss in their relative wage positions, are also more likely to have a wage cut associated with their job-to-job transition. The overall results therefore suggest that the status effect is dominated by an opposing signal effect.
Keywords: D03; J31; J62; J63; M52; 330; comparison income; mobility; signaling; status; wages; Lohnstruktur; Erwerbsstatus; Arbeitszufriedenheit; Arbeitsmobilität; Deutschland